Using Randomized Controlled Trials for Treatment Decisions - Gerald Crites; Laurel Murrow; Julie Gaines; Jennifer Stowe; W. Scott Richardson (Association of American Medical Colleges, 2016)
Abstract Introduction Numerous studies have demonstrated that many physicians lack fundamental skills of interpreting and using clinical care evidence. Building a foundation for evidence-based medicine (EBM) will provide an initial scaffold that can be integrated during later clinical training. We built this module as a two-session experience to provide first- or second-year medical students the opportunity to build fundamental knowledge about treatment clinical research and how to appraise randomized trials. Methods The first session of the module consists of a didactic or prerecorded online didactic to review basic concepts and principles about treatment research. The second session is an in-class exercise where students may take preparatory quizzes to assess readiness followed by an application exercise where teams of seven to eight students appraise a randomized trial. The module design uses several team-based learning (TBL) principles, and the module can be slightly modified to use the traditional TBL method if time permits. The module also includes two practice exercises and several supplementary learning resources. Results We have been teaching this module to first- and second-year medical students for 9 years and have made several iterative improvements. No students have failed the courses within which this module is integrated. The module individual quizzes have averaged 60%-100%, the group quizzes > 80%, and the application exercises > 80%. We performed a pre-post assessment of alternative multiple-choice question items (10 pre, 10 post) covering the same objectives for a recent student cohort. The mean premodule scores were 47.7% and the mean postmodule scores were 71.3%. Discussion We have used this module successfully for 9 years to teach treatment evidence. This resource represents the culmination of our collective experience with this topic. This module can be taught as a stand-alone session but is better integrated with other EBM modules (e.g., risk trials, prognosis trials, searching, etc.) to provide comprehensive knowledge about how to acquire and understand all the variables that are considered for clinical decisions.